Biosynthesis, characterization, and in-vitro anticancer effect of plant-mediated silver nanoparticles using Acalypha indica Linn: In-silico approach - Luailik Madaniyah; Saidun Fiddaroini; Elok Kamilah Hayati; Moh. Farid Rahman; Akhmad Sabarudin (OpenNano)
Cancer is a significant global health issue, with rising prevalence and mortality rates demanding urgent attention. The World Health Organization emphasizes the need for effective prevention, early detection, and treatment strategies to address this public health challenge. Current treatment modalities, including surgery, hormonal therapy, immunotherapy, radiation therapy, and chemotherapy, are often associated with considerable side effects and high costs. This study investigates the biosynthesis of silver nanoparticles using Acalypha indica L. (AgNPs), a medicinal plant recognized for its therapeutic benefits, as a potential cancer treatment with minimal side effects and a lower risk of drug resistance. AgNPs exhibit anti-inflammatory properties and the ability to inhibit angiogenesis while counteracting drug resistance mechanisms. Moreover, the use of chitosan as a coating on AgNPs (AgNPs-Chit) enhances their stability and specificity toward cancer cells, thereby improving their anticancer efficacy. Characterization of the synthesized AgNPs was conducted using various techniques, including UV-Vis spectroscopy, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), particle size analysis (PSA), and transmission electron microscopy (TEM), confirming the successful synthesis, stability, and spherical morphology of the nanoparticles, with an average diameter of 7 nm and a zeta potential of −24.51 mV. In vitro cytotoxicity testing showed that AgNPs-Chit exhibited stronger anticancer activity against T47D cells with an IC50 value of 173 µg/mL, compared to AgNPs (IC50 244 µg/mL) and the Acalypha indica L extract (IC50 826 µg/mL). When compared to the control, treatments with AgNPs-Chit, AgNPs, and the plant extract demonstrated statistically significant differences (∗p < 0.05, ∗∗p < 0.01). These results indicate that the modification of AgNPs with chitosan (AgNPs-Chit) significantly enhances anticancer efficacy compared to both AgNPs and Acalypha indica L. extract. The modification with AgNPs increased anticancer efficiency by 338%, while AgNPs-Chit showed a 446% increase compared to the original extract, highlighting the enhanced potential of these nanoparticles in inhibiting cancer cell growth. Additionally, molecular docking studies of eight key compounds identified through LC-MS analysis (quercetin, kaempferol, catechin, indoline, 4-aminobenzoic acid, 1-(2-quinolinyl)piperazine, 3-indoleacrylic acid, and pyridine-3-carboxamide) revealed strong binding affinities to the cancer target protein 3PP0, with binding energies ranging from −9.4 to −5.9 kcal/mol, compared to doxorubicin's binding energy of −9.0 kcal/mol.